Serum amylin levels in patients with multiple sclerosis - Ufuk Cinkir; Levent Sinan Bir; Selma Tekin; Ahmet Magrur Karagulmez; Esin Avci Cicek; Hande Senol (Medicine, 2026)
Amylin is a pancreatic neuroendocrine peptide that links peripheral metabolic regulation with central homeostatic and neurodegenerative pathways. However, its relevance to the inflammatory and demyelinating processes underlying multiple sclerosis (MS) remains unclear. To date, the role of amylin in MS has not been investigated. This study investigated serum amylin levels in patients with MS and their association with disease status. This cross-sectional case-control study included 62 patients meeting the 2017 McDonald criteria for MS and 63 control participants without MS or associated risk factors. Serum amylin levels were measured using enzyme-linked immunosorbent assay (ELISA). Between-group and phenotype-specific differences were examined. Multivariable logistic regression and receiver operating characteristic (ROC) curve analyses were performed to assess the association between serum amylin and MS status, and the discriminatory performance of serum amylin, respectively. Serum amylin levels were determined in both groups and reported as mean values. Mean serum amylin levels were significantly lower in patients with MS than in controls (234.01 ± 94.84 vs 284.04 ± 110.02 ng/L; P = .003). The groups were comparable across the principal anthropometric, metabolic, and biochemical variables assessed. No significant differences were observed among the relapsing–remitting, secondary progressive, and primary progressive MS (PPMS) phenotypes; however, pairwise analysis demonstrated a significant difference between the relapsing–remitting MS (RRMS) subgroup and controls ( P = .017). In multivariable analysis, higher serum amylin levels remained independently associated with lower odds of MS after adjustment for aspartate aminotransferase (AST) activity ( P = .02). Despite the significant between-group difference, serum amylin demonstrated only modest discriminatory performance ( P = .003). Lower circulating amylin levels were associated with MS status, although their modest discriminatory performance does not support the use of serum amylin as a standalone diagnostic marker, based on the present data. The phenotype-specific difference observed in RRMS warrants further investigation in larger, longitudinal, and clinically characterized cohorts. These findings may deepen insights into MS development and support future biomarker research.